Hiattville, Bourbon County - Davis, Jenee (Kansas State University, The Chapman Center for Rural Studies, 2015)
This brief history of Hiattville uncovers its struggles to recover from a series of devastating fires, especially the fires of 1905 and 1913. Although a promising railroad town in Bourbon County in 1890s, by the 1920s, Hiattville was in a long, slow decline. This study relies on a county history, historical maps, and many newspaper articles.
Jenee Davis, “Hiattville, Bourbon County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/167.
Keywords: Bourbon County; Fort Scott; Hiattville; Hiattville Weekly Optic; Kansas School Unification Act; Pawnee Township